2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00693
|View full text |Cite
|
Sign up to set email alerts
|

Photon-Flooded Single-Photon 3D Cameras

Abstract: Single-photon avalanche diodes (SPADs) are starting to play a pivotal role in the development of photon-efficient, long-range LiDAR systems.However, due to nonlinearities in their image formation model, a high photon flux (e.g., due to strong sunlight) leads to distortion of the incident temporal waveform, and potentially, large depth errors. Operating SPADs in low flux regimes can mitigate these distortions, but, often requires attenuating the signal and thus, results in low signal-to-noise ratio. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…On the other hand, returning signal photons from the true laser peak add up "coherently" because their bin location remains fixed. Asynchronous acquisition with uniform shifting achieves lower error than synchronous acquisition with no and extreme attenuation [13], over a wide range of flux conditions. As a result, the accumulated histogram has enough photons in all bins ( Fig.…”
Section: Photon Pileup: Prevention Better Than Cure?mentioning
confidence: 96%
See 4 more Smart Citations
“…On the other hand, returning signal photons from the true laser peak add up "coherently" because their bin location remains fixed. Asynchronous acquisition with uniform shifting achieves lower error than synchronous acquisition with no and extreme attenuation [13], over a wide range of flux conditions. As a result, the accumulated histogram has enough photons in all bins ( Fig.…”
Section: Photon Pileup: Prevention Better Than Cure?mentioning
confidence: 96%
“…Photon pileup mitigation for SPAD cameras: Perhaps the most widely adopted approach for preventing pileup is attenuation, i.e., optically blocking the total photon flux incident on the SPAD so that only 1-5% of the laser pulses lead to a photon detection [2,3]. 1 Recent work [14,13] has shown that this rule-of-thumb extreme attenuation is too conservative and the optimal operating flux is considerably higher. Various computational [25,14] and hardware [1,3,35] techniques for mitigating pileup have also been proposed.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations